Sound Horeg In The Perspective of Maqāṣid Al-Sharī'ah: Analysis of The East Java MUI Fatwa Number 1 Of 2025 - Hendri; Busyro; Ismail; Mohd Taufik Harun (Muhammadiyah University of Surabaya, 2026)
The phenomenon of using sound horeg in East Java society gave birth to social and health polemics, so the East Java Indonesian Ulema Council (MUI) forbade it through Fatwa No. 1 of 2025. This article aims to examine the ijtihad method used in the determination of the East Java MUI fatwa No. 1 of 2025 and how from the perspective of maqāṣid al-syarī'ah. The research method uses a qualitative approach based on literature study and content analysis of fatwas, complemented by fiqh rules and sharī'i arguments. The results show that the ijtihad of MUI East Java is contextual with the following steps taḥqīq al-manāṭ through an assessment of the social impact of high-volume sound and istinbāṭ al-aḥkām using qiyas coupled with the fiqh rule of dar'ul mafsadid muqaddamun 'ala jalbil maṣāliḥ (preventing harm takes precedence over attracting maslahat), maqashid sharia analysis that sound horeg is only tabi’iyyah (entertainment, prestige), while the harm touches ashliyyah (protecting the soul, protecting the mind, protecting property, and maintaining order). Therefore, MUI East Java's fatwa No. 1 of 2025 is the result of integrative contemporary ijtihad, combining classical sharia texts with modern social reality. This shows a methodological shift in fatwa from merely normative to responsive, by prioritizing the principle of maqāṣid al-syarī'ah as the main instrument to maintain the benefit of the people. Keywords: Sound Horeg, Maqashid Al Shari’ah, Fatwa, Indonesian Ulama’ Council.